2019
DOI: 10.5650/jos.ess18251
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Olive Varieties on Fatty Acid Composition and Tocopherol Contents of Cold Pressed Virgin Olive Oils

Abstract: INTRODUCTION Olea europaea is one of the most important and widespread fruit trees in the Mediterranean basin. Virgin olive oil is a quite valuble oil extracted from olives using cold press, which is the best practise for minimizing the loss of bioactive constituents 1 4. The major component of olive oil is triacylglycerols, which form by esterification of fatty acids and glycerol and also comprise more than 98 of total compounds, phytochemicals are significant minor components of olive oil 2. This chemical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…Α-Tocopherol contents were directly related to the contents of vitamin E in the almonds themselves. The same observations were seen in several seeds, fruits, and kernel oils, such as apricot kernels, pumpkin seeds, avocado, and olives (Manaf et al, 2018;Matthäus & Musazcan Özcan, 2015;Matthäus et al, 2016;Nakić et al, 2006;Özcan et al, 2019;Wen et al, 2016).…”
Section: Geographic and Weather Conditions And Crop Year Genotypes An...supporting
confidence: 69%
“…Α-Tocopherol contents were directly related to the contents of vitamin E in the almonds themselves. The same observations were seen in several seeds, fruits, and kernel oils, such as apricot kernels, pumpkin seeds, avocado, and olives (Manaf et al, 2018;Matthäus & Musazcan Özcan, 2015;Matthäus et al, 2016;Nakić et al, 2006;Özcan et al, 2019;Wen et al, 2016).…”
Section: Geographic and Weather Conditions And Crop Year Genotypes An...supporting
confidence: 69%
“…so we can conclude that phenol content showed marked variations with plant growth, in fact probably the phenol storage in the leaves is a time dependent regulated process, according to the life cycle of olive leaves. In addition Özcan et al. (2019) demonstrated that fatty acid composition and phenols contents of the olive oils showed differences depending on the olive variety.…”
Section: Resultsmentioning
confidence: 97%
“…In fact, according to the life cycle of olive leaves, the phenol storage in the leaves is probably a time‐dependent regulated process. In addition, Ozcan et al showed that phenol contents and fatty acid composition of the olive oils may differ according to olive variety (Özcan et al., 2019).…”
Section: Resultsmentioning
confidence: 99%